Обеспечение производственной мощности глубоких карьеров путем применения КНК и скиповых подъемников - Медведева, О.А. (Геотехническая механика, 2011)
В статті наведено про складність видобутку руди на глибоких горизонтах кар’єру, а також технологію з використанням круто похилих конвеерыв або скіпових підйомних установок. The article describes the complexity of the mining pit in the deeper horizons as well as unsubstantiated capacity of deep pits in the application of high-angle conveyors or skip hoists.